PERAN MEDIA PEMBELAJARAN INTERAKTIF DALAM MENGATASI KESULITAN BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Aisyah, Aisyah; Putri, Hafiziani Eka; Ardelia, Afifah; Pangestu, Olga; Somantri, Syahla Mecca Putri; Farid, Ramzy Sukri (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to describe the role of interactive learning media in overcoming elementary students’ difficulties in learning mathematics. The main focus is on how interactive media can simplify complex mathematical concepts, increase students’ interest in learning, and reduce their anxiety. The research employed a literature review method to analyze the role of interactive learning media in addressing mathematics learning difficulties. The procedure involved identifying keywords, searching sources from databases published between 2020 and 2025, selecting relevant studies, and conducting content analysis. Data analysis was carried out by collecting, reviewing, and comparing previous studies. The findings indicate that interactive learning media play a strategic role as an effective solution. Both concrete media (manipulative teaching aids) and digital media (interactive applications and animations) function as bridges connecting abstract mathematical concepts with more concrete learning experiences, aligned with elementary students’ cognitive development. The use of these media helps reduce difficulties in understanding concepts, confusion in problem-solving procedures, and feelings of fear or low confidence in learning. Overall, interactive learning media contribute significantly to improving students’ understanding, motivation, and self-confidence. Therefore, the planned and contextual integration of interactive media is a pedagogical necessity to minimize learning barriers and enhance the quality of mathematics understanding in elementary schools.